Increased CNTF levels in adults with autism spectrum disorders - Brondino, Natascia; Rocchetti, Matteo; Fusar-Poli, Laura; Damiani, Stefano; Goggi, Arianna; Chiodelli, Giuseppe; Corti, Serafino; Visai, Livia; Politi, Pierluigi (The world journal of biological psychiatry, 2019)
Ciliary neurotrophic factor (CNTF) is a neurotrophin which could signal neuronal suffering and at the same time acts as a neuroprotective agent. In the present study we aimed to evaluate CNTF serum levels in autism spectrum disorders (ASDs). In fact, considering the role of CNTF as a neuronal damage signal and the role of neuroinflammation, excito-inhibitory imbalance and excitotoxicity in the pathogenesis of ASDs, a possible alteration of CNTF in ASDs could be hypothesised. We recruited 23 individuals with ASDs and intellectual disability (ID), 20 ID subjects and 26 typical adults. A complete medical and psychopathological characterisation of the participants was performed. CNTF serum levels were measured with ELISA. CNTF serum levels were significantly higher in the ASD + ID group compared to ID ( < .001) or typically developed subjects ( < .001). CNTF may be considered as a potential biomarker candidate for ASDs in the context of severe ID. Our results support the hypothesis of neurotrophic imbalance in ASDs.